Transformation of Islamic Religious Education Learning in the Era of Society 5.0: A Theoretical and Conceptual Study - Izzatul Laili; Tomi Apra Santosa; Hasyim Mahmud Wantu; Busnawir Busnawir (Published by Institut Teknologi Pendidikan Indonesia, 2026)
The Society 5.0 era presents fundamental changes in various aspects of life, including the education sector. The integration of digital technology, artificial intelligence (AI), the Internet of Things (IoT), and big data demands a transformation in the Islamic Religious Education (PAI) learning process to remain relevant to the needs of 21st-century students. This study aims to theoretically and conceptually analyze the transformation of Islamic Religious Education (PAI) learning in the Society 5.0 era and its implications for student competency development. This study used a qualitative approach with library research methods. Data were obtained from various literature sources, such as books, reputable journal articles, education policy documents, and scientific publications relevant to Islamic Religious Education (PAI) learning and Society 5.0. Data analysis was conducted using content analysis techniques to identify key themes related to the transformation of Islamic Religious Education (PAI) learning. The study results indicate that the transformation of Islamic Religious Education (PAI) learning in the Society 5.0 era is characterized by the use of digital technology in the learning process, strengthening digital and religious literacy, implementing student-centered learning models, and integrating Islamic values with 21st-century competencies. Furthermore, the role of teachers has shifted from being primary sources of information to facilitators, mentors, and spiritual guides capable of guiding students in the wise and ethical use of technology.